Polarization signatures of Mars dust and clouds: Prospects for future spacecraft observations. (July 2021) - Jaiswal, Bhavesh; Mahapatra, G.; Nandi, Anuj; Sudhakar, M.; Sankarasubramanian, K.; Sheel, V.
Abstract: The study of polarized sunlight scattered from planetary atmospheres provides diagnostic tools that can help explore the possible composition and size distribution of clouds and aerosol particles. Previous studies have shown the potential of this technique in studying Water clouds on Earth and in the discovery of Sulphuric Acid clouds on Venus. The atmosphere of Mars is unique as it hosts three different types of aerosols: water (H2 O) ice, carbon dioxide (CO2 ) ice and dust. We considered scenarios analogous to Martian conditions and calculated the single and multiple scattering polarization for Martian dust, water ice and carbon dioxide ice with the help of a Radiative Transfer algorithm for Nadir and Limb spacecraft observation positions. The polarization features (-Q/I) of Mars atmosphere have low amplitude and have been found to be within the range of ±0.1 in the Nadir/Limb geometry for the spherical, spheroidal and cylindrical shapes considered here. We study its dependence upon the observation geometry, shape, size and composition of the scatterer. Future spacecraft studies of microphysical properties of dust and clouds through polarization will reveal the nature of condensation processes active in the Martian atmosphere. Highlights: A detailed theoretical study of polarization signatures of Mars atmosphere. Consideration of various size distributions, shapes and atmospheric configurations (like dust or clouds). Mars atmospheric polarization (-Q/I) is found to be constrained within +0.1 to −0.1 in near infrared for various observation geometries and shapes of the dust and clouds. Non-spherical particle shapes (more likely for solid aerosols of Mars) offering large polarization features at around 90° scattering angles, which is missed by Earth based observations, can be effectively probed by spacecraft observation. These predictions will help future exploration of Mars atmosphere for better understanding of dust and clouds.